Lessons learned in using realist evaluation to assess maternal and newborn health programming in rural Bangladesh - Adams, Alayne; Sedalia, Saroj; McNab, Shanon; Sarker, Malabika (Health Policy and Planning, 2016)
Includes bibliographical references (page 8-9).